Degradation Of Lampung Language On Marga Sekampung Community In Gunung Raya East Lampung - Septiyana, Linda; Sari, Yeasy Agustina; Muhammad, Hasanuddin (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
This study aims to: 1) describe the existence of Lampung language on Marga Sekampung community in Gunung RayaÂ  2) analyze the factors that influence the Lampung language degradation on Marga Sekampung community in Gunung Raya. This study is a qualitative research. This study was carried out in Gunung Raya, Marga Sekampung, East Lampung. The findings of this study are 1) the existence of Lampung language on Marga Sekampung community in Gunung Raya in the cultural and social environment so far is still well maintained. However, there is a language shifting in the existence of Lampung language of Marga Sekampung community in family environment, especially the use of the Lampung language between parents and children as well as the use of Lampung Language between children and children. 2) The factors that influence the Lampung language degradation Â on Marga Sekampung community in Gunung Raya especially on children or teenangers are their own selves factors, lack of socialization in the family environment, and interaction with their friends. Based on the results of this study, it should be for children and parents of Marga Sekampung community in Gunung Raya get used to using Lampung language in their daily life so that it does not become extinct.